New Strategies for the Treatment of Diabetic Foot Ulcers Using Nanoenzymes: Frontline Advances in Anti-Infection, Immune Regulation, and Microenvironment Improvement - Jia S; Wu S; Yi M; Jiang Z; Cai X; Chen S; Li Y (International Journal of Nanomedicine)
Shuyu Jia,1– 3 Siyu Wu,4 Min Yi,1 Ziqi Jiang,1 Xinyu Cai,1 Shutong Chen,1 Yingzhi Li1– 3 1Orthopaedic Medical Center, The Second Norman Bethune Hospital of Jilin University, Changchun, 130041, People’s Republic of China; 2Joint International Research Laboratory of Ageing Active Strategy and Bionic Health in Northeast Asia of Ministry of Education, Jilin University, Changchun, Jilin Province, 130041, People’s Republic of China; 3Jilin Provincial Key Laboratory of Orthopaedics, Changchun, People’s Republic of China; 4Department of Hand Surgery, The Second Hospital of Jilin University, Changchun, 130041, People’s Republic of ChinaCorrespondence: Yingzhi Li, Orthopaedic Medical Center, The Second Norman Bethune Hospital of Jilin University, Changchun, 130041, People’s Republic of China, Email dlyz2005@jlu.edu.cnAbstract: Diabetic foot ulcers are one of the most serious consequences of diabetes, arising from vascular impairment of the skin and disturbances in the microenvironment. This condition involves pathological changes such as wound infection, hyperglycemia, hypoxia, oxidative stress, and cellular dysfunction, necessitating multifaceted interventions. Traditional treatments often target only the wound itself, resulting in limited effectiveness. In contrast, nanoenzymes offer a promising therapeutic option due to their excellent biocompatibility and tissue permeability. They exhibit higher catalytic efficiency, optimal size and structure, and improved stability compared to natural enzymes. Encapsulating various nanoenzymes within novel biomaterials can enhance therapeutic outcomes through antibacterial action, glycemic control, oxygen delivery, antioxidative effects, anti-inflammatory properties, and angiogenesis promotion. This approach represents a key direction for future diabetic wound treatment. This article summarizes the role of nanoenzymes in diabetic wound management and discusses the potential mechanisms of their action. We also provide an outlook on their application prospects, aiming to advance their clinical utilization. Keywords: chronic wound, hyperglycemia, oxidative stress, antibacterial action, angiogenesis